2015
DOI: 10.1007/s40037-015-0178-8
|View full text |Cite
|
Sign up to set email alerts
|

What is more effective: a daily or a weekly formative test?

Abstract: BackgroundExams in anatomy courses are traditionally summative. Formative testing induces retrieval practice, provides feedback and enhances learning results. We investigated the optimal frequency for retrieval practice during an anatomy course.MethodDuring a first-year course, students were offered four online daily quizzes a week that assessed thoracic anatomy. Once a week they received a quiz about abdominal anatomy. Students immediately received feedback afterwards. In the fourth course week, a survey abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 22 publications
1
14
1
Order By: Relevance
“…Previous studies indicated that the participation rate in formative quizzes was correlated to summative examination scores (Kibble, 2007;Palmen et al, 2015). The present study did not confirm this finding.…”
Section: Journal Of Educational Issuescontrasting
confidence: 99%
See 3 more Smart Citations
“…Previous studies indicated that the participation rate in formative quizzes was correlated to summative examination scores (Kibble, 2007;Palmen et al, 2015). The present study did not confirm this finding.…”
Section: Journal Of Educational Issuescontrasting
confidence: 99%
“…This may relate to the ISSN 2377-22632016 voluntary aspect and immediate feedback after TOPday quizzes. The observed increase in enthusiasm and appreciation for (digital) study aids is in line with other studies (Evans, Zeun, & Stanier, 2014;Palmen, Vorstenbosch, Tanck, & Kooloos, 2015). The rationale for this approach was to increase the students' motivation for repetitive learning and to give them an opportunity for self-assessment, which fits in the recent changes of the medical curriculum at the Radboudumc.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The effectiveness of test‐enhanced learning practices has been conclusively demonstrated in studies on medical residents where their implementation enabled the retention of intermediate, late, and long‐term factual and conceptual anatomical knowledge (Palmen et al, ; Hulbert and Anderson, ). In addition, these students also reported significantly higher efficiency (Joshi et al, ), enjoyment (Shatto and Erwin, ), and satisfaction (Calvin and McDowell, ; Tetenbaum‐Novatt et al, ) in the learning process.…”
Section: Stimulating Intrinsic Motivation In Millennial Studentsmentioning
confidence: 99%